Control of Cellular Differentiation Trajectories for Cancer Reversion - Jeong‐Ryeol Gong; Chun‐Kyung Lee; Hoon‐Min Kim; Juhee Kim; Jaeog Jeon; Sunmin Park; Kwang‐Hyun Cho (Advanced Science)
Abstract Cellular differentiation is controlled by intricate layers of gene regulation, involving the modulation of gene expression by various transcriptional regulators. Due to the complexity of gene regulation, identifying master regulators across the differentiation trajectory has been a longstanding challenge. To tackle this problem, a computational framework, single‐cell Boolean network inference and control (BENEIN), is presented. Applying BENEIN to human large intestinal single‐cell transcriptome data, MYB, HDAC2, and FOXA2 are identified as the master regulators whose inhibition induces enterocyte differentiation. It is found that simultaneous knockdown of these master regulators can revert colorectal cancer cells into normal‐like enterocytes by synergistically inducing differentiation and suppressing malignancy, which is validated by in vitro and in vivo experiments.